2006
DOI: 10.1111/j.1360-0443.2006.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the acute subjective effects of MDMA/ecstasy

Abstract: This review provides useful information for clinicians and researchers who want to understand the desirable and undesirable ASEs that may motivate and restrain ecstasy use, for public health advocates who seek to reduce biomedical harms (e.g. fainting, dehydration, shortness of breath, bruxism) associated with recreational use of MDMA/ecstasy, and for educators who wish to design credible prevention messages that neither underestimate nor exaggerate users' experiences of this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 49 publications
10
99
2
4
Order By: Relevance
“…Findings are also consistent with reports that women experience more acute negative effects of recreational ecstasy [7,8] and with animal studies demonstrating that the behavioral effects of MDMA are greater in females [9]. Contrary to the findings of Liechti et al [1], we found that females also exhibited greater cardiovascular responses to the drug than males.…”
Section: Discussioncontrasting
confidence: 56%
“…Findings are also consistent with reports that women experience more acute negative effects of recreational ecstasy [7,8] and with animal studies demonstrating that the behavioral effects of MDMA are greater in females [9]. Contrary to the findings of Liechti et al [1], we found that females also exhibited greater cardiovascular responses to the drug than males.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous research in ecstasy users has found that users of the drug report disturbed sleep both as a primary subjective effect (Baylen & Rosenberg, 2006;Huxster et al 2006;Montoya et al 2002) and a longer lasting psychobiological complaint (Parrott et al 2006). The present study found some support for sleep differences in ecstasy users.…”
Section: Discussionmentioning
confidence: 99%
“…Primary evidence from subjective accounts of ecstasy users suggests that they are aware that they have less sleep when using than when not using ecstasy. Baylen and Rosenberg (2006) reviewed 24 studies of the acute subjective effects of ecstasy (i.e. occurring within 24 hours after use).…”
Section: Introductionmentioning
confidence: 99%
“…This result was not due to an unspecific increase of motor activity, as no increase in the number of total or closed entries was observed in animals treated with both drugs. Although numerous studies have indicated that MDMA causes anxiety problems in drug users (for review see Baylen et al, 2006), our results revealed that MDMA alone does not exert a strong effect on levels of anxiety in adolescent mice. The few studies performed in the plus maze with mice have shown that acute MDMA administration induces anxiogenic or anxiolytic effects that vary depending on the dose employed (Navarro et al 2002).…”
Section: Mdma Plus Cocainementioning
confidence: 65%